1997
DOI: 10.1073/pnas.94.20.10833
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory oligodeoxynucleotides containing the CpG motif are effective as immune adjuvants in tumor antigen immunization

Abstract: Recent advances in our understanding of the immune response are allowing for the logical design of new approaches to cancer immunization. Bacterial DNA is capable of inducing activation of B cells, NK cells, and monocytes (1-5). In addition, bacterial DNA can induce production in vitro and in vivo of a variety of proinflammatory cytokines (6-8). In contrast, vertebrate DNA does not induce lymphocyte activation. Bacterial DNA contains a much higher frequency of unmethylated CpG dinucleotides than does vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
254
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 467 publications
(265 citation statements)
references
References 24 publications
7
254
0
3
Order By: Relevance
“…It has been reported that nonmethylated palindromic DNA containing CpG-ODN can activate an innate immune response by activation of NK cells, DC and B cells in an antigen-independent manner (Weiner et al, 1997). Recognition of these microbial sequences is mediated by a member of the TLR family, namely TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nonmethylated palindromic DNA containing CpG-ODN can activate an innate immune response by activation of NK cells, DC and B cells in an antigen-independent manner (Weiner et al, 1997). Recognition of these microbial sequences is mediated by a member of the TLR family, namely TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that bacterial DNA and synthetic oligodeoxynucleotides (ODNs) containing specific motifs centered on a CpG dinucleotide (CpG ODNs) are potent immunostimulatory agents (1)(2)(3)(4)(5). Unmethylated CpG sequences are present at a frequency of 1 in every 16 dinucleotides in bacteria, while mammals have a CG dinucleotide suppression with only one-fourth of the expected frequency, and the majority of the CpG sequences are methylated in mammals (6).…”
mentioning
confidence: 99%
“…Unmethylated CpG sequences are present at a frequency of 1 in every 16 dinucleotides in bacteria, while mammals have a CG dinucleotide suppression with only one-fourth of the expected frequency, and the majority of the CpG sequences are methylated in mammals (6). CpG ODNs act rapidly on a variety of cell types such as B cells, natural killer (NK) cells, and antigen-presenting cells including monocytes, macrophages, and dendritic cells (5,7). CpG mediates its effect through Toll-like receptor 9 (TLR-9) (8), initiating a rapid inflammatory response and production of cytokines such as interleukin-6 (IL-6), IL-12, IL-1, interferon-␥ (IFN␥), and tumor necrosis factor ␣ (TNF␣) (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…CpG motifs are short oligonucleotides where a 2′-deoxycytidine is connected by a phosphodiester bond to 2′-deoxyguanosine. When these nucleotides are unmethylated as in natural viral and bacterial DNA they have immunostimulatory activity [54]. This CpG motif occurs very rarely in vertebrate genomes and is therefore considered a pathogen-associated molecular pattern indicating invasion of pathogens [55].…”
Section: Dna Tetrahedramentioning
confidence: 99%